Tribomechanical Properties of Polymeric Composites Based on Mixture of Ultra High Molecular Weight Polyethylene and Polyamide - Panin S. V. Sergey Viktorovich; Kornienko L. А.; Thuc N. X.; Ivanova L. R.; Poltaranin M. A.; Shilko S. V. (Materials Science in Mechanical Engineering, 2015)
Title screen